Asthma Risk Prevalence and Associated Factors in Stunted Children: A Study Using Asthma Predictive Index - Gartika Sapartini; Gary W. K. Wong; Agnes Rengga Indrati; Cissy B. Kartasasmita; Budi Setiabudiawan (Medicina)
Background and Objectives: The prevalence of stunted children under 5 years in Indonesia is relatively high. Stunting is a significant risk factor for wheezing disorders. The asthma predictive index (API) identifies children with a recurrent wheezing disorder at risk of developing asthma during the first 3 years. However, the risk of developing asthma and its associated factors among stunted children has not been studied. This study aims to determine the asthma risk prevalence in stunted children via the API score and associated factors. Materials and Methods: This cross-sectional study was conducted at the Bandung District Health Center from October 2021 to January 2022. This study included stunted children aged 24–59 months living in Bandung District whose parents could answer the API and asthma risk factor questionnaires. Results: A total of 422 participants with an average age of 43.1 ± 9.7 months were included. Among the stunted children, 4.7% (20/422) met the positive API criteria, and 50.0% were malnourished (stunted–underweight). The participants with positive API results had a parental medical diagnosis of asthma (45%), eczema (10.0%), allergic rhinitis (20.0%), and wheezing apart from colds (40.0%) (p < 0.05). Significant risk factors for developing asthma in the participants with a positive API were dog ownership in the past 12 months and parents and siblings with allergic diseases. Conclusions: The asthma risk prevalence in stunted children was 4.7%. The associated risk factors included a history of allergic diseases in parents and siblings, as well as dog ownership; however, further investigation is needed.